MEMBANGUN PSIKOLOGI ISLAMI - Aziz, Rahmat (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2004)
It is the fact, that the thought of western psychology has expand speedy, and adopted by many scholars, include us. However, it does not mean that there is no flawed in western psychology. For instance, Freud’s psychoanalysis is considered over simplified and cannot explain some problems such as fitrah in Islam, John Lock’s behaviorist did not admit human intrinsic potencies which empirically cannot be denied, in addition, humanistic of Maslow have ignored factor and the role of God in the human life.Islamic psychology comes into being to respond for the lack of western psychology theories. There are two ways in developing Islamic psychology; praxis and theoretic. Praxis method means developing Islamic psychology based on what have been developed by western psychology then we filter it and search the legitimacy for it; meanwhile, theoretic method means developing Islamic psychology based on the teaching and resources of Islamic knowledge itself. Keyword: Psychology, Western, and Islam.